The socio-environmental environment of social support networks for long-life people and the Nicoya Peninsula, Costa Rica, from the perspective of the basic model of capabilities - Cavallini Solano, Hennia (2022)
The following document develops an ethnographic analysis of information collected from the biological, physical, and social areas related to older adults in the Costa Rican Blue Zone located in the Nicoya Peninsula, and includes the counties of Nicoya, Santa Cruz, Hojancha, Nandayure, and Carrillo. The data collection    is carried out through a semi-structured interview, which combines qualitative techniques of ethnography and basic quantitative information gathering about social support networks. Also, specific data on noise, relative humidity, temperature, luminosity and CO are collected from the localities in order to understand the physical context of the long-lived individuals and their support networks. Once the data are collected, an systematized, through which basic sub-dimensions are determined. These point out the route indicators that lead to identifying the dimensions of Senses and Imagination, Emotions, Affiliation, Life Health and Body Integrity, and Environment Control, which reveal the capabilities model of this longevity band.